Imagining Emergent Metadata, Realizing the Emergent Web - Bengtson, Jason A. (My University, 2012)
While metadata is a key ingredient of machine-semantic technologies, it has drawbacks. As it is currently formed, metadata lacks dynamic responsiveness and requires top-down system modeling. The author proposes a schema and process of emergent metadata that will, if successful, allow metadata to respond to environmental conditions dynamically and to exhibit self-organizational features.
Citation: Bengtson, Jason. "Imagining Emergent Metadata, Realizing the Emergent Web." Journal of Library Metadata 12.4 (2012) : 345-361. Print.
Keywords: Complexity Science; Emergence; Information Science; Metadata; Search and Discovery; Self Organization